Cyclophosphamide-induced seizures in a patient with neuropsychiatric systemic lupus erythematosus (NPSLE): A case report - Zhang, Lingshu; Shi, Ying; Zhang, Jingyao; Wu, Jing; Jiang, Wei (Frontiers in Immunology, 2023)
Seizures are life-threatening complications of neuropsychiatric systemic lupus erythematosus (NPSLE) and are often associated with poor outcomes. Cyclophosphamide immunotherapy is the mainstay of NPSLE treatment. We report the unique case of a patient with NPSLE who developed seizures soon after her first and second doses of low-dose cyclophosphamide. The exact pathophysiological mechanism underlying cyclophosphamide-induced seizures is not well understood. However, this unusual drug-associated side effect of cyclophosphamide is thought to be due to the drug’s unique pharmacology. Clinicians should be aware of this complication to make a correct diagnosis and adjust the immunosuppressive regimens very carefully.